Early life stress induces irritable bowel syndrome from childhood to adulthood in mice - Tao, Enfu; Wu, Yuhao; Hu, Chenmin; Zhu, Zhenya; Ye, Diya; Long, Gao; Chen, Bo; Guo, Rui; Shu, Xiaoli; Zheng, Wei; Zhang, Ting; Jia, Xinyi; et al. (Frontiers in Microbiology, 2023)
Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal disorder. Traditionally, early life stress (ELS) is predisposed to IBS in adult. However, whether ELS induces IBS in early life remains unclear.Separated cohort studies were conducted in neonatal male pups of C57BL/6 mice by maternal separation (MS) model. MS and non-separation mice were scheduled to be evaluated for prime IBS-phenotypes, including visceral hypersensitivity, intestinal motility, intestinal permeability, and anxiety-like behavior. Ileal contents and fecal samples were collected and analyzed by 16S rRNA gene sequencing and bacterial community analyses. Subcellular structures of intestinal epithelial, such as epithelial tight junctions and mitochondria, were observed under transmission electron microscopy.MS induced visceral hypersensitivity and decreased total intestinal transit time from childhood to adulthood. In addition, MS induced intestinal hyperpermeability and anxiety-like behavior from adolescence to adulthood. Besides, MS affected intestinal microbial composition from childhood to adulthood. Moreover, MS disrupted intestinal mitochondrial structure from childhood to adulthood.The study showed for the first time that MS induced IBS from early life to adulthood in mice. The disrupted intestinal mitochondrial structure and the significant dysbiosis of intestinal microbiota in early life may contribute to the initiation and progress of IBS from early life to adulthood.